(untitled) - Wyman, J. Robert (Boston, 2000)
This quick reference is designed specifically for security professionals who have safety responsibilities in general industry - offices, retail, manufacturing, and other industrial facilities. In a climate of profit driven business challenges, the policies that ensure human welfare should not be difficult to implement. Safety Strategies for the Security Professional presents the daily disciplines of OSHA-compliant safety strategies in a concise and practical manner. With more than a decade of experience in asset protection management, J. Robert Wyman brings the fundamental concepts of safety back into the reach of all safety managers, security professionals, and operations managers who hold the responsibility for occupational health.
Keywords: Industrial hygiene,Industrial safety,Bảo hộ lao động,An toàn công nghiệp; United States,United States.,Nước Mĩ,Nước Mĩ